Facial identity and facial expression are initially integrated at visual perceptual stages of face processing. (8th January 2016) - Fisher, Katie; Towler, John; Eimer, Martin
Abstract: It is frequently assumed that facial identity and facial expression are analysed in functionally and anatomically distinct streams within the core visual face processing system. To investigate whether expression and identity interact during the visual processing of faces, we employed a sequential matching procedure where participants compared either the identity or the expression of two successively presented faces, and ignored the other irrelevant dimension. Repetitions versus changes of facial identity and expression were varied independently across trials, and event-related potentials (ERPs) were recorded during task performance. Irrelevant facial identity and irrelevant expression both interfered with performance in the expression and identity matching tasks. These symmetrical interference effects show that neither identity nor expression can be selectively ignored during face matching, and suggest that they are not processed independently. N250r components to identity repetitions that reflect identity matching mechanisms in face-selective visual cortex were delayed and attenuated when there was an expression change, demonstrating that facial expression interferes with visual identity matching. These findings provide new evidence for interactions between facial identity and expression within the core visual processing system, and question the hypothesis that these two attributes are processed independently. Highlights: Interference between identity and expression is symmetrical during face matching. N250r components index perceptual identity matching process in visual face memory. N250r components are delayed and attenuated by changes of expression. Face identity matches are processed regardless of task-relevance. Face identity and expression are integrated during early visual perception.